The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/advs.201800006
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 7‐Derived Peptides Play a Vital Role in Vascular Repair and Regeneration

Abstract: Cardiovascular disease is a leading cause of morbidity and mortality globally. Accumulating evidence indicates that local resident stem/progenitor cells play an important role in vascular regeneration. Recently, it is demonstrated that a histone deacetylase 7‐derived 7‐amino acid peptide (7A, MHSPGAD) is critical in modulating the mobilization and orientated differentiation of these stem/progenitor cells. Here, its therapeutic efficacy in vascular repair and regeneration is evaluated. In vitro functional analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 44 publications
(61 reference statements)
2
26
0
Order By: Relevance
“…Modification of synthetic grafts aims at promoting homing of progenitor cells by delivering chemotaxis factors or stem cell activators have been pursued as potential means to regenerate functional artery. [ 17,18 ] However, the critical roles of the immune cells widely playing roles in adult tissues repair, especially during biomaterial mediated regeneration, are scarcely considered.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of synthetic grafts aims at promoting homing of progenitor cells by delivering chemotaxis factors or stem cell activators have been pursued as potential means to regenerate functional artery. [ 17,18 ] However, the critical roles of the immune cells widely playing roles in adult tissues repair, especially during biomaterial mediated regeneration, are scarcely considered.…”
Section: Introductionmentioning
confidence: 99%
“…Our research has shown that 7Ap treatment improved the capillary density and promoted neovascularization at the border zone of the ischemic heart. In a parallel study [12], we have demonstrated that the inclusion of 7A, especially the phosphorylated version, 7Ap, significantly increased endothelialization. The majority of the endothelial cells derived from the local resident Sca-1 + stem cells of the surrounding tissues, because 7Ap can serve as a chemoattractant for Sca-1 + stem cells and direct their differentiation toward the EC lineage.…”
Section: Discussionmentioning
confidence: 76%
“…The phosphorylated 7A (7Ap, MH[pSer]PGAD) was shown to increase stem cell migration, proliferation, and differentiation, especially that of vascular progenitor cells (VPCs). 7Ap enhanced angiogenesis, ameliorated vascular injury and promoted blood perfusion recovery in in a femoral artery injury model and a hindlimb ischaemia model [12]. According to the properties of 7Ap, in this study, we speculated that the peptide should greatly contribute to MI therapy.…”
Section: Introductionmentioning
confidence: 70%
“…Recently, we published some data on the role of 7A in EC differentiation and its contribution to tissue engineered vessel graft 21 and protection in cardiac fibrosis via hydrogel implication. 22 In this study, we focused on the demonstration of the translation of the 7A peptide and its function in signal transduction and vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%